2004
DOI: 10.1182/blood-2004-02-0666
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-specific Bcl-2 overexpression attenuates ischemia-reperfusion injury, immune response during acute rejection, and graft coronary artery disease

Abstract: After cardiac transplantation, graft damage occurs secondary to ischemia-reperfusion injury and acute rejection. This damage ultimately leads to the development of graft coronary artery disease (GCAD), which limits long-term graft survival. Apoptosis is directly involved in graft injury, contributing to the development of GCAD. To assess the role of the antiapoptotic factor Bcl-2 in the process of GCAD, we transplanted hearts from FVB transgenic mice overexpressing human Bcl-2 under the control of ␣-myosin hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 40 publications
3
36
0
2
Order By: Relevance
“…Hypertension produces collagen deposition, changes referred to as myocardial fibrosis, which leads to depressed myocardial performance (Bu et al, 2008). Some studies indicated that ISO-induced acute myocardial infarction after ischemia is caused by myocardial hyperactivity and coronary hypertension (Yeager and Iams, 1981), the inflammatory response (Steffens et al, 2009) and cell apoptosis (Tanaka et al, 2004). In this study, the reduced inflammatory cellular infiltration, myocardial necrosis, and fibrosis in SIM pre-treated rats (group IV) confirmed the cardio-protective effect of SIM.…”
Section: Discussionsupporting
confidence: 77%
“…Hypertension produces collagen deposition, changes referred to as myocardial fibrosis, which leads to depressed myocardial performance (Bu et al, 2008). Some studies indicated that ISO-induced acute myocardial infarction after ischemia is caused by myocardial hyperactivity and coronary hypertension (Yeager and Iams, 1981), the inflammatory response (Steffens et al, 2009) and cell apoptosis (Tanaka et al, 2004). In this study, the reduced inflammatory cellular infiltration, myocardial necrosis, and fibrosis in SIM pre-treated rats (group IV) confirmed the cardio-protective effect of SIM.…”
Section: Discussionsupporting
confidence: 77%
“…*P \ 0.05, **P \ 0.01 vs. sham group; P \ 0.05, P \ 0.01 vs. CON group; à P \ 0.05, àà P \ 0.01 vs. IL group overexpression of Bcl-2 in cardiomyocytes suppresses I/R injury in transgenic mice. 27 By contrast, pro-apoptotic Bax serves as an inducer of apoptosis to counteract the action of Bcl-2, and the ratio of Bcl-2/Bax determines cell survival or death. 28 A limited number of previous studies have shown that isoflurane may be capable of protecting hearts against apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is still widely controversial whether the phosphorylation of Bcl-2 is a pro-apoptotic or anti-apoptotic event. The Bcl-2 family of proteins regulates apoptosis by controlling mitochondrial permeability and the release of cytochrome c. 20 The anti-apoptotic proteins of Bcl-2 reside in the outer mitochondrial wall and inhibit cytochrome c release. Figure 6 provides a summary of possible apoptosis activation pathways after CBC/CPB observed.…”
Section: Discussionmentioning
confidence: 99%